Introduction - Mitsi, E., et al. (Ruins in the Literary and Cultural Imagination, 2019)
Taking as a point of departure Lord Byron’s reflections on the meaning of the ruined Parthenon, this essay traverses the long legacy of ruin-thinking in the Anglo-American imagination, and argues for its relevance to the present day. Referencing earlier and recent strands in the rich scholarship on the trope of the ruin, the authors contextualize the essays of the volume; particular emphasis is laid on the volume’s especial focus on the ruin as metaphor and as a historical materiality, as these are probed in individual chapters that discuss ruin and ruination across British and American literature, continental theory and philosophy.